Significance of the indexing of the Peruvian Journal of Gynecology and Obstetrics to Scopus - Romero, José Pacheco (2023)
The Peruvian Journal of Gynecology and Obstetrics (RPGO, for its acronym in Spanish)has obtained its inclusion in the important Scopus database. A quick review of thejournal's publication recalls the editorial dedication of its six editors, four of whomhad just recently chaired the Peruvian Society of Obstetrics and Gynecology (SPOG,for its acronym in Spanish). The initial editorial work was carried out manually, ontypewriters and continuously visiting the printing press, as well as the sponsors.The commitment of the SPOG Steering Committees to finance the publicationand distribution of the issues allowed the gradual indexing to local, regional andinternational databases. Its internalization was expanded since the publication ofthe RPGO in the Open Journal Systems (OJS), a computer system where articles arepublished with punctuality, quality, including their editorial characteristics and theInformation for Authors. Now the publication is only virtual, in English and Spanish,with visibility and impact of the articles since the beginning of the RPGO in 1955. Withupdated OJS data on the RPGO, the number of monthly visits to the abstracts reachesup to 10 thousand and monthly downloads of articles in PDF format reach more than9 thousand. And, in the field of obstetrics and gynecology scientific journals in LatinAmerica and Spain in Scopus, the h index of the RPGO by Google Scholar Metricsstands out as one of the best. At present, and facing future challenges, the activity ofthe RPGO has been strengthened, establishing an editorial team and tools that allowthe already initiated professionalization of the processes of the editorial activity.